2016
DOI: 10.1007/s00221-016-4775-5
|View full text |Cite
|
Sign up to set email alerts
|

Posture interacts with arm weight support to modulate corticomotor excitability to the upper limb

Abstract: The use of arm weight support (WS) to optimize movement quality may be an avenue for improved upper limb stroke rehabilitation; however, the underlying neurophysiological effects of WS are not well understood. Rehabilitation exercises may be performed when sitting or standing, but the interaction of posture with WS has not been examined until now. We explored the effect of posture with WS on corticomotor excitability (CME) in healthy adults. Thirteen participants performed static shoulder abduction in two post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
2
4
1
Order By: Relevance
“…The number of synergies expressed by the moderate-severe impairment group did not respond to changes in WS, likely because of neuroanatomical constraints on available substrates for motor control. In the control group, WS affected CME (MEP area) measured in all muscles except ECR, similar to previous studies with WS and younger participants (Runnalls et al, 2014;2017).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The number of synergies expressed by the moderate-severe impairment group did not respond to changes in WS, likely because of neuroanatomical constraints on available substrates for motor control. In the control group, WS affected CME (MEP area) measured in all muscles except ECR, similar to previous studies with WS and younger participants (Runnalls et al, 2014;2017).…”
Section: Discussionsupporting
confidence: 89%
“…A similar argument could explain why ECR CME did not respond to WS in the control and mild groups (Table 4). In contrast, previous experiments with healthy adults found that ECR CME was modulated by WS (Runnalls et al, 2014;2017). Although it is unknown which factors may account for the discrepancy between studies, the present findings provide evidence in support of an indirect modulation of neural excitability distinct from changes in muscle activity.…”
Section: Direct and Indirect Effects Of Weight Supportcontrasting
confidence: 96%
See 2 more Smart Citations
“…Although many functional tasks are performed in standing (e.g., meal preparation at the kitchen counter), most measurement of the upper extremity function in clinical and research settings occurs in sitting. Research suggests that the performance of skilled arm and hand movements in standing differs from the same movements in sitting (Berrigan et al, 2006; Cuisinier et al, 2005), requires precise coordination between upper extremity movement and postural control (Chen et al, 2016; Pozzo et al, 2002), and is associated with changes in corticomotor excitability for upper extremity muscles (Kantak et al, 2013; Runnalls et al, 2017). The impact of standing on the control of upper extremity tasks may be magnified in individuals with neurologic conditions such as stroke, who often present with postural control deficits (Belgen et al, 2006; Harris et al, 2005; Jorgensen et al, 2002; van de Port et al, 2006).…”
Section: Introductionmentioning
confidence: 99%